Isolated coronary arteritis secondary to Behçet’s disease: a case report - Yang ZHANG; Lei XU; Xinying HU; Hao JIANG; Feng ZHANG; Junbo GE (Zhongguo Linchuang Yixue)
A 36-year-old male patient presented with repeated myocardial infarction. Despite regular dual-antiplatelet therapy and intensive lipid-lowering therapy, he still experienced restenosis after coronary stent implantation. He then transferred to the Zhongshan Hospital, Fudan University. According to the disease history, combined with coronary artery inflammation observed by PET/CT and effective anti-inflammatory treatment, he was finally diagnosed with Behçet’s disease (BD) combined with isolated coronary arteritis. BD has been included in the Chinese Second Catalog of Rare Diseases, and the disease that only involves the coronary arteries is even rarer, which makes it very easy to misdiagnose and underdiagnosis in clinical practice. Strengthening the understanding of the complex clinical phenotypes of various vasculitis, attaching importance to multidisciplinary consultation, and dynamically following up are of great value for the early diagnosis of this disease.